STRATEGI KOMUNIKASI DALAM ADVOKASI HASIL PENELITIAN (Studi : Mahasiswa Klinik Hukum Anti Korupsi Fakultas Hukum UNPAD) - Nur Atnan (Kanal: Jurnal Ilmu Komunikasi, 2015)
This study aims to identify and analyze the preparation phase before a student advocate research results (pre-advocacy research), activities during the students deliver research results to the agency (advocacy research result), as well as post-delivery activities of the research results at the agency (post-advocacy research results). This study used a qualitative method. A qualitative approach through interviews and researcher are involved in every student advocacy activities. The results showed that the main component in the communication strategy for the Anti Corruption Legal Clinic Students in the Faculty of Law, Padjadjaran University in 2014, in the form of communication planning, implementation, and evaluation. Initial activities is done by the students were doing research as a strength in the form of the evidences. At the implementation phase, the students prepared a full report and presentation materials research. Then, at this evaluation phase has not been done optimally because it is constrained by the limitations of time. The conclusions of the study showed that overall in each strategy were not optimal yet.